PENGGUNAAN ALAT PERAGA CONTOH BATUAN (ROCK HAND SPECIMENT)DALAM PEMBELAJARAN MATA DIKLAT PENGENALAN BAHAN BAKU BATUAN DAN MINERAL BATUMULIA - Mirna Mariana (PPSDM Geominerba, 2019)
The research on the use of rock hand specimen in subject learning “introduction of rock and gemstones minerals as material” is to overcome learning difficulties in subject learning. The research is using Class Action Research (CAR) with model descriptive with quantitative method approach. This type of research includes the Class Action Research starting from the planning, implementation, observation, and reflection stages. Classroom Action Research Method is a research that consists of one or more cycles of action depends on the problem you want to solve. The process of Classroom action research is proven to improve learning outcomes. The value of learning outcomes using method pretest, and without using rock hand specimen, obtained an average score of 32% correctly answering. The value of learning outcomes during cycle 1 (using rock hand specimen per group 6–7 participant with of 3types of rock units). In that cycle, an average score of 62% was answered correctly. So the research continue to the cycle 2. The value of learning outcomes at the time of cycle 2 (using rock hand specimen per person with 3 types of rock units. In cycle 2 obtained an average score of 94% correctly answered.